Circular Directed Suction Technique for Ablative Laser Treatments. Issue 8 (8th April 2013) - Wagner, Justinus A.; Bodendorf, Marc O.; Grunewald, Sonja; Simon, Jan C.; Paasch, Uwe
Abstract : Background: The use of ablative laser treatments is steadily increasing. A side‐effect is plume, which can potentially transmit infectious material. Insufficient plume removal may lead to transmission of infectious diseases. Objective: To introduce a newly developed circular suction technique for ablative interventions. Materials and Methods: The new plume removal system consists of a circular master tube and four smaller suction tubes. This design guarantees plume removal around the whole treatment area. This system can be connected in principle to any common aspiration device. The suction system worked effectively with perfect satisfaction in daily routine. Its effect on skin surface temperature was evaluated using thermography and surface temperature measurements. Results: The circular system removed the laser‐associated plume much better than ordinary single‐point plume‐removal systems. Split‐face investigations confirm additional benefits in terms of better skin surface cooling. Conclusion: The combination of providing a cool air flow during laser treatment and circular suction is a new approach for directed cooling air streams and streamed plume evacuation without obstructing the physician because of its architecture.